Locating Alpha-bungarotoxin in 2-DE Gel of Bungarus multicinctus (Many Banded Krait) Venom - J, Vejayan; H, brahim; I, Othman (Malaysian Journal of Science, 2008)
Snake venom being one of the most prominent subsets of natural toxins, has been extensively studied as it causes many crippling injuries and death to mankind. It is a well-known fact that snake venom is the most complex of all known toxins. In this study identification of a lethal protein in snake venom was carried out using the integrated approach of proteomics. Initially, 2D gel electrophoresis, a component of proteomics, was used to separate low molecular weight proteins from Bungarus multicinctus venom. Next, the location of alpha-bungarotoxin was determined by spiking this protein together with B. multicinctus venom using the sample cup loading technique. An image based 2D analysis of B. multicinctus venom only and that spiked with alpha-bungarotoxin showed a 2.5 fold increase in % volume of one spot. Consequently, identification of this protein spot using 'matrix-assisted laser desorption ionization-time of flight (MALDI- TOF) mass spectrometry', matched it to alpha-bungarotoxin. This study demonstrated the usefulness of proteomics in locating the position of important proteins in 2D map of a complex sample such as that of snake venoms